Pelatihan Penyusunan Laporan Keuangan Sesuai SAK EMKM Bagi Pengurus Bumdes Ralmida Desa Tounwawan Pulau Moa Kabupaten Maluku Barat Daya - Janet Wilsye Litualy; Sitti Fatimah Kamaruddin; Engrith Grafelia Leunupun; Thimotina Killay; Fanny Monica Anakotta; Dwi Kiswantini; Lenci Madiuw (Lembaga Pengembangan Kinerja Dosen, 2026)
Raining on the preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) for the management of Village-Owned Enterprises (BUMDes) is one of the community service programs aimed at improving the ability of BUMDes administrators in preparing financial statements in accordance with applicable accounting standards. In this activity, SAK EMKM serves as a guideline in preparing more transparent and accountable financial reports. This program is expected to provide a positive impact on village financial management while strengthening the performance of BUMDes in carrying out its role as a driver of the village economy. The activity was implemented through a practical approach involving BUMDes administrators directly. The training was complemented with simulations and case studies to help participants better understand the process of preparing financial statements based on SAK EMKM. In addition, this training also aimed to increase the awareness of BUMDes administrators regarding the importance of accountability and transparency in financial management as part of efforts to achieve good village governance.